Levels of childhood nutritional status among the Muslims of char areas in Barpeta district, Assam - Begum, Gulrukh (International Journal Of Community Medicine And Public Health, 2019)
Background: The chars depend mostly on the whims of the current of river. The location, delicate ecological conditions and the political situation arising out of the ill- defined problem of immigration have collectively made the chars of Barpeta a challenging place to live. The worst sufferers are the children before entering adolescence period. This study aims to assess the level of nutritional status among the pre-adolescent children. Methods: 466 children (250 boys and 216 girls) from age 3 to10 years were measured cross-sectionally for their height and weight. Sample was collected from Chasra No. 2 char which fall under Baghbor revenue circle of the district. Using Z-score value, the underweight, wasting and stunting status was evaluated. Results: It has been detected that 39.2% boys and 18.98% girls are underweight. The percentage of stunted among them is 16% for the boys and 12.96% for the girls. With the increase of age the prevalence of stunting has decreased. BMI-for -age has detected 24% boys and 24.53% girls to be affected. When the children of the present study were compared with other populations, they were below the tribal children but above other children in their nutritional status. Conclusions: The prevalence of stunting is lesser than underweight percentage, reflecting their current nutritional status to be more affected than the long term exposure to undernutrition. The prevalence of underweight and stunting is higher among the boys than the girls. Further analytic studies are required to identify the underlying causes of their status.